Dynamic characteristics and components selection strategy of a railway vehicle quarter car suspension - Ahmed, Md Iqbal; Md. Yusof, Hazlina; Rashid, Muhammad Mahbubur (International Conference on Intelligent Unmanned Systems (ICIUS), 2015)
Suspension system is a mechanism which isolates the vehicle body from road shocks and unwanted vibrations. A basic suspension system usually consists of spring, damper, rods, and ball joints in both automotive and railway transportation. The primary aim of this project is to design and develop a smallscale test rig of quarter car railway vehicle for suspension system. This paper describes the research investigation, the technical design procedure and component selection strategy of the completed suspension system. The rig design and motion analysis has been done by using Solidworks motion study to find out the dynamic characteristic of the system such as estimation of torque requirement, vehicle body and bogie acceleration, vehicle body and bogie displacement based on the selected parameters and track input.